2018
DOI: 10.6007/ijarbss/v8-i11/4896
|View full text |Cite
|
Sign up to set email alerts
|

Tax Planning and Firm Value: Evidence from Malaysia

Abstract: The main objective of this study is to determine the impact of tax planning on firm value of firms listed in Bursa Malaysia. Tax planning proxies in this study are the Effective Tax Rate (ETR) and Book Tax Differences (BTDs). The 387 samples data were collected from the DataStream from period of 2014 to 2016. After controlling the firm size, leverage, asset tangibility, firm age and dividend, the regression results show that ETR has a significant and positive relationship with firm value while BTDs has insigni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 17 publications
2
16
0
3
Order By: Relevance
“…The research showed that effective tax rates positively and significantly affected firm value. Razali et al (2018) investigated the effect of tax planning on firm value by using a sample of 387 firms listed in Bursa Malaysia from 2014 to 2016, and confirmed that the effective tax rate positively linked to firm value.…”
Section: Literature Reviews and Hypotheses Developmentmentioning
confidence: 85%
“…The research showed that effective tax rates positively and significantly affected firm value. Razali et al (2018) investigated the effect of tax planning on firm value by using a sample of 387 firms listed in Bursa Malaysia from 2014 to 2016, and confirmed that the effective tax rate positively linked to firm value.…”
Section: Literature Reviews and Hypotheses Developmentmentioning
confidence: 85%
“…The results contradict the findings of De Jong et al (2011) and Gonzales (2013) revealed that debt positively influences the value of a company. Oeta, et al (2019), Timothy, et al (2020), Izevbekhai & Odion (2018); Razali, et al (2018) findings suggest a negative insignificant relationship between financial leverage and value of a firm.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Variabel independen tingkat penghindaran pajak dihitung dengan BTD. Perhitungan selisih laba akuntansi dan fiskal dibagi total aset (Razali et al, 2018). Variabel mediasi yang digunakan yaitu biaya agensi, dihitung dengan penjualan dibagi total aset, untuk melihat seberapa baik perusahaan menggunakan asetnya.…”
Section: Metodologi Penelitianunclassified
“…positif yang mana artinya bahwa dengan menghindari pajak akan meningkatkan nilai perusahaan nilai perusahaan tersebut. Lalu penelitian lainnya Razali et al (2018) dengan data di Malaysia menunjukkan bahwa dengan 2 proxy berbeda untuk menghitung penghindaran pajak menghasilkan hasil yang berbeda.…”
unclassified